The Role of Chemokine Receptor CXCR7 in Lung Cancer - Jun LIU; Fu-rong ZHANG; Yue LI; Chang-li WANG (Cancer Biology & Medicine, 2010)
OBJECTIVE To investigate whether CXCL12 and its receptor, CXCR7, play a role in lung cancer invasion and metastasis.METHODS Western blot and immunocytochemistry were used to detect CXCR7 protein expression in 8 lung cancer cell lines, EKVX, HOP62, HOP92, NCI-H23, NCI-H226, NCI-H322M, NCI-H446, and A549, and cell migration experiment was conducted to observe mobility of the lung cancer cells. The concentration of intracellular calcium in cytoplasm was measured under the fluorescence microscopy.RESULTS CXCR7 protein was positively expressed in the 8 lung cancer cell lines EKVX, HOP62, HOP92, NCI-H23, NCI-H226, NCI-H322M, NCI-H446, and A549. Following CXCL12 stimulation, obvious pseudopodia of lung cancer cells was observed under the microscope. The cell migration experiment showed that after incubation with CXCL12, the number of EKVX cells, which passed through the polycarbonate microporous filter membranes increased to a great extent. This phenomenon can be reversed by CXCR7-siRNA. After CXCL12 incubation, the intracellular Ca2+ level in the EKVX cells was increased to a great extent. CONCLUSION Chemokine CXCL12 facilitates the migration of lung cancer cells by changing the concentration of intracellular Ca2+. The CXCL12-CXCR7 axis may play an important role in lung cancer invasion and metastasis. It could be a potential target for lung cancer therapy and an effective way to prevent recurrence and metastasis of lung cancer.